PRE-ROUND WARM UP ROUTINE: EFFECTS ON AVERAGE DRIVING DISTANCE, PUTTING STROKES AND REGULATIONS OF GOLFERS - Umar Farooq; ZubiaSavila; Noor Muhammad Marwat; Ejaz Asghar; Muhammad Zubair; Khawar Ehsan; Habib Ullah (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Warm up is an act of preparing yourself for a physical activity. Every golfer performs a specific warm up routine to enhance performance and to prevent him self from injuries.The physical demands required by the body to perform a round of golf arehuge. Few hours before playing a round of golf has a great impact on performance. Evidence proves that different warm up protocols have a great influence on golfin ground.Currently there is no study conduct edu sing professional golfers to research effect of pre round warm up routine on performance so,therefore, the purpose of this research is to assess the effect of pre-round warm-up routineonthreedifferentcomponentsofperformancesuchasaveragedriving distance, putting strokes, and regulations amonggolfers. Twenty male golfers divided into two groups experimental and control participated. Experiment group performed proper pre-round warm up routine for three consecutive days. The results showed that the participants of experimental groupwhoperformedpreroundwarmuproutine,theiraveragedrivingdistance, green in regulation, fairway in regulation increased and putting strokes decreasedduetowhichtheperformanceimproved.